Principiile care guvernează procesul electoral în Republica Moldova - Smochină, Andrei; Cebanu, Ion (My University, 2021)
This article elucidates the main legal regulations on the electoral process that were provided by the main electoral law of the Republic of Moldova — the Electoral Code and the amendments to this law from 1997 to the present. We placed special emphasis on the principles governing the organization and conduct of elections in the Republic of Moldova. We consider these fundamental ideas as the basis of the electoral legislation from which the whole democratic process on which the whole mechanism of the state apparatus is based should start.

Acest articol elucidează principalele reglementări juridice în materie de proces electoral care au fost prevăzute de principala lege electorală a Republicii Moldova – Codul Electoral și de modificările aduse acestei legi din 1997 până în prezent. Un accent deosebit am pus pe principiile care guvernează organizarea și desfășurarea alegerilor în Republica Moldova. Consider aceste idei fundamentale, drept baza legislației electorale de la care ar trebui să pornească întreg procesul democratic pe care se întemeiază tot mecanismul aparatului de stat.
PRINCIPLES GOVERNING THE ELECTORAL PROCESS IN THE REPUBLIC OF MOLDOVA
Keywords: principles; electoral process; elections; uninominal voting; proportional voting; constituency; electoral code; electoral rights; principii; proces electoral; alegeri; vot uninominal; vot proporțional; circumscripție electorală; cod electoral; drepturi electorale